Diversity and Potential Analysis of Liquid Biopesticide Bacteria for Fusarium sp. Control of Shallot -Basal Rot - Nur Aini; Suharjono (Biotropika: Journal of Tropical Biology, 2024)
Shallot basal rot disease (Allium cepa L.) caused by the fungus Fusarium causes many crop losses thus control efforts are required. Microbial biopesticides are used as an alternative to control pests and plant pathogens that are environmentally friendly and target-specific. This study aims to evaluate the diversity of liquid biopesticide bacteria and their potential to control the Fusarium sp. pathogen of shallots. This study includes shallot sampling, isolation, and purification of liquid biopesticide bacteria, liquid biopesticide antifungal test, double culture antagonistic test of bacterial isolates against Fusarium sp., and identification of potential bacterial isolates based on 16S rDNA sequence similarity. The results showed that two bacterial isolates, B7 and B2, had the highest importance value index of 94.21% and 90.59%, respectively, with a bacterial diversity index of 1.44. Liquid biopesticide microbial biomass has a high inhibition zone in the antifungal test against Fusarium sp. with an average inhibition zone of 6.45 mm. Bacterial isolate B2 has the highest potential inhibition of 71.3% against Fusarium sp. and was identified as Genus Serratia with a similarity value of 96.79%.